Acute recreational drug and new psychoactive substance toxicity in Europe: 12 months data collection from the European Drug Emergencies Network (Euro-DEN). (21st October 2015) - Dines, Alison M; Wood, David M; Yates, Christopher; Heyerdahl, Fridtjof; Hovda, Knut Erik; Giraudon, Isabelle; Sedefov, Roumen; Dargan, Paul I; ,
Abstract : Context. Despite the potential for recreational drugs and new psychoactive substances (NPSs) to cause significant morbidity and mortality, there is limited collection of systematic data on acute drug/NPS toxicity in Europe. Objective. To report data on acute drug/NPS toxicity collected by a network of sentinel centres across Europe with a specialist clinical and research interest in the acute toxicity of recreational drugs and NPS to address this knowledge gap. Methods. Sixteen sentinel centres in 10 European countries (Denmark, Estonia, France, Germany, Ireland, Norway, Poland, Spain, Switzerland and the UK) collected data on all acute drug toxicity presentations to their Emergency Rooms (ERs) for 12 months (October 2013–September 2014); information on the drug(s) involved in the presentations was on the basis of patient self-reporting. Results. Data were collected on a total of 5529 presentations involving 8709 drugs (median (interquartile range [IQR]): 1 (1–2) drugs per presentation), a median of 0.3% of all ER attendances. Classical recreational drugs were most common (64.6%) followed by prescription drugs (26.5%) and NPS (5.6%). The 'top five' drugs recorded were heroin (1345 reports), cocaine (957), cannabis (904), GHB/GBL (711) and amphetamine (593). 69.5% of individuals went to hospital by ambulance (peak time between 19:00 and 02:00 at weekends); the median (IQR) age was 31 (24–39) years and 75.4% were male. Although serious clinical features were not seen in most presentations and 56.9% were medically discharged from the ER (median length of stay: 4.6 hours), a significant number (26.5%) was agitated, in 10.5% the GCS was 8 or less and 35 presented in cardiac arrest. There were 27 fatalities with opioids implicated in 13. Conclusion. The Euro-DEN dataset provides a unique insight into the drugs involved in and clinical pattern of toxicity/outcome of acute recreational drug toxicity presentations to hospitals around Europe. This is complimentary to other indicators of drug-related harm and helps to build a fuller picture of the public health implications of drug use in Europe.